Impact of nutritional knowledge on dietary behaviors of students in Kuwait University - Almansour, Fawaz D.; Allafi, Ahmad R.; Al-Haifi, Ahmad R. (Acta Biomedica Atenei Parmensis, 2020)
Increasing nutritional knowledge is an important component of broader societal efforts to address the high prevalence of nutrition-related diseases. In Kuwait, university students are a critical target group since many of their lifestyle behaviors are shaped during college and may continue throughout their life. The aim of this study was to explore the effects of nutritional knowledge on the dietary behavior of 700 undergraduate students of Kuwait University. Nutritional knowledge and dietary behavior of Kuwait University undergraduate students were evaluated using paper-based questionnaires to assess lifestyle and nutrition behavioral changes. Students who experienced better dietary habits had better nutritional knowledge. However, the strength of the association was considered weak (r=0.229). The findings suggest that nutritional knowledge can slightly assist in adopting healthier eating habits, which may reduce nutrition-related diseases. Therefore, nutrition education programs and nutritional activities in classes should be recommended among students to promote healthy lifestyles.